2016
DOI: 10.1177/0149206314522301
|View full text |Cite
|
Sign up to set email alerts
|

All Work and No Play? A Meta-Analytic Examination of the Correlates and Outcomes of Workaholism

Abstract: Empirical research on workaholism has been hampered by a lack of consensus regarding the definition and appropriate measurement of the construct. In the present study, we first review prior conceptualizations of workaholism in an effort to identify a definition of workaholism. Then, we conduct a meta-analysis of the correlates and outcomes of workaholism to clarify its nomological network. Results indicate that workaholism is related to achievement-oriented personality traits (i.e., perfectionism, Type A perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
786
4
71

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(918 citation statements)
references
References 125 publications
(195 reference statements)
57
786
4
71
Order By: Relevance
“…Both variables significantly negatively correlated with detachment from work. Recent meta-analyses found that people with higher values on these variables report more severe experiences of negative emotions (DeNeve and Cooper, 1998; Clark et al, 2016) and work stressors (Bowling et al, 2015; Clark et al, 2016). Thus, our results underline the assumption of Sonnentag and Fritz (2015) that person characteristics related to appraisal processes of the work situation might further influence detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Both variables significantly negatively correlated with detachment from work. Recent meta-analyses found that people with higher values on these variables report more severe experiences of negative emotions (DeNeve and Cooper, 1998; Clark et al, 2016) and work stressors (Bowling et al, 2015; Clark et al, 2016). Thus, our results underline the assumption of Sonnentag and Fritz (2015) that person characteristics related to appraisal processes of the work situation might further influence detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Although structural equation models were estimated controlling for the effect of a possible confounder such as gender (Jex et al, 2002), it is also possible that the transitory mood of the respondents (i.e., the mood mechanism; Spector et al, 2000b) or other individual characteristics, such as workaholism (i.e., the tendency to work beyond what is reasonably expected because of internal pressures and to have persistent thoughts about work when not working, Clark et al, 2014), may confound the relationship between NA, stressors and pro-inflammatory cytokines (Clark et al, 2014;Falco et al, 2013a;Falvo et al, 2013;Kravina et al, 2010Kravina et al, , 2014. A future diary study could clarify the unique contribution of NA, transitory mood and workaholism in the relationship between stressors and the strain response.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been an increasing number of studies exploring the problem of excessive work and work addiction over the past 2 decades, contrary to other behavioral addictions, there are many unanswered questions related to the psychology of work addiction [6]. For instance, only a few studies have investigated the psychological antecedents of work addiction in a longitudinal context (see review by Clark et al [7]). Consequently, the personality factors involved in the development of work addiction are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, only the term "work addiction" is used because this term is theoretically based on the core addiction literature, whereas workaholism typically refers to excessive working independently from its negative or positive consequences [6]. During the past 4 decades, several definition and conceptualization have been developed relating to work addiction [7]. As Clark et al [7] emphasized, these can differentiate between theories regarding work addiction as an addiction [19,20], as a behavioral pattern [21], as a set of attitudes toward work [22], and as a syndrome [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation